Banks' Survival during the Financial Crisis: The Role of Regulatory Reporting Quality - NG, Jeffrey (Institutional Knowledge at Singapore Management University, 2012)
In this paper, we investigate the effect of bank transparency before the crisis on bank stability during the financial crisis that erupted in 2008. Using a large sample of private and public commercial banks in the United States, we find that transparency enhances stability. We use two measures of transparency. We develop a new measure of financial reporting transparency based on loan loss provision estimation errors. We corroborate our findings using a second measure based on the incidence of accounting restatements. We show that lower transparency before the crisis is associated with higher non-performing loans and lower profitability at the onset of the crisis. We document that banks with lower transparency are more likely to experience regulatory intervention through enforcement actions and bank failures during the crisis. We also find some evidence that higher transparency improves the effectiveness of regulatory enforcement actions.